Surveys of cassava plantations in Colombia for virus and virus- like diseases - Nolt, Barry L.; Pineda López, Benjamín; Velasco, Ana Cecilia (Wiley, 1992)
Abstract in: Biological Abstracts Vol. 94 Ref. 66670